Islands in the stream. - Scott, George C., 1927-; Roland, Gilbert, 1905-; Hemmings, David, 1941-; Hemingway, Ernest, 1899-1961.; Paramount Pictures Corporation; Paramount Home Video ([New York, N.Y.] : Paramount Home Video, 1979)
Thomas Hudson, an artist living on an island retreat, is visited by his three sons for the summer. During that time, they overcome anger and disappointment as they become aware of their mutual love and needs.
VHS format release of 1977 film.
George C. Scott, David Hemmings, Gilbert Roland, Claire Bloom.
Keywords: Feature films